Uji Aktivitas Antimikroba Fraksi Daun Jeruk Lemon (Citrus limon (L.) Osbeck) terhadap Stapylococcus aureus dan Escherichia coli - Siti Rachmawati; Winda Oktima; Pangeran Andareas (Pro-Life, 2021)
Infection is a condition where the entry of microorganisms into the body's tissues, multiplies and causes disease in the form of disruption of body functions. Lemon leaves (Citrus limon (L.) Osbeck) are plants that have the potential to have antimicrobial power in the presence of bioactive compounds. The purpose of this study was to determine the antimicrobial activity of lemon fraction against Staphylococcus aureus and Escherichia coli. Ethyl acetate fraction is more effective in inhibiting bacteria, compared to ethanol and n-hexane extract based on preliminary tests conducted. Disk diffusion antimicrobial activity test (Kirby-Bauer) was used at a concentration of 5% the ethyl acetate fraction effectively inhibited Staphylococcus aureus bacteria with a diameter of inhibition zone was 12.3 mm while the Escherichia coli bacteria was 8.7 mm at a concentration of 25%. The results of data analysis using One-Way ANOVA (analysis of variance) showed a significant difference based on variations in concentration in inhibiting Staphylococcus aureus and Escherichia coli.